Accuracy of implant surgical guides fabricated using computer numerical control milling for edentulous jaws: a pilot clinical trial - Jinyou Chai; Xiaoqian Liu; Ramona Schweyen; Jürgen Setz; Shaoxia Pan; Jianzhang Liu; Yongsheng Zhou (BMC, 2020)
Abstract Background To evaluate the accuracy of a computer numerical control (CNC) milled surgical guide for implant placement in edentulous jaws. Methods Edentulous patients seeking implants treatment were recruited in this prospective cohort study. Radiographic guides with diagnostic templates were fabricated from wax-up dentures. Patients took cone-beam computed tomography (CBCT) wearing the radiopaque radiographic guides. Implant positions were virtually designed in the planning software based on the CBCT data, and the radiographic templates were converted into surgical guides using CNC milling technique. Forty-four implants were placed into 12 edentulous jaws following guided implant surgery protocol. Post-surgery CBCT scans were made for each jaw, and the deviations between the planned and actual implant positions were measured. Deviation of implant position was compared between maxilla and mandible, and between cases with and without anchor pins using independent t-test. Results Nine patients (3 males and 6 females) with 12 edentulous jaws were recruited. The mean age of patients was 59.2 ± 13.9 years old. All 44 implants was placed without complication and survived, the mean three dimensional linear deviation of implant position between virtual planning and actual placement was 1.53 ± 0.48 mm at the implant neck and 1.58 ± 0.49 mm at the apex. The angular deviation was 3.96 ± 3.05 degrees. No significant difference was found in the deviation of implant position between maxilla and mandible (P = 0.28 at neck, 0.08 at apex), nor between cases with and without anchor pins (P = 0.87 at neck, 0.06 at apex). Conclusions The guides fabricated using the CNC milling technique provided comparable accuracy as those fabricated by Stereolithography. The displacement of the guides on edentulous arch might be the main contributing factor of deviation. Trial registration: Chinese Clinical Trial Registry, ChiCTR-ONC-17014159 (July 26, 2017).